Hydroxychloroquine enhances efferocytosis and modulates inflammation via MerTK/Gas6 signaling in a pristane-induced lupus mouse model - Liu, Shin-Yi; Yeh, Yung-Ju; Xue, Ting-Yin; Hsieh, Fei-Hung; Wu, Ya-Wun; Wu, Meng-Zhen; Li, Wei-Jing; Tsay, Jun-Chieh J.; Tsai, Shu-Yao; Huang, Chung-Ming; Chang, Hen-Hong; Chen, Hui-Chen; et al. (Frontiers in Immunology, 2025)
BackgroundHydroxychloroquine (HCQ) is a frontline treatment for autoimmune diseases, including rheumatoid arthritis, Sjogren’s syndrome, and systemic lupus erythematosus (SLE), due to its potent immunomodulatory properties. Efferocytosis, a crucial process for tissue homeostasis by transmitting immune-suppressive signals, is frequently impaired in SLE. We hypothesized HCQ enhances efferocytosis and mediates anti-inflammatory effects.MethodsA pristane-induced lupus (PIL) mouse model was used to assess the preventive efficacy of HCQ by measuring inflammatory cytokine levels, autoantibody titers, and lupus nephritis severity. Efferocytosis in HCQ-treated macrophages was quantified following co-incubation with apoptotic cells and the expression levels of TAM family receptors post-HCQ stimulation were analyzed in vitro and in vivo. The role of MerTK on HCQ-modulated inflammation was revealed by MerTK inhibitor UNC2025.ResultsLong-term HCQ treatment in PIL mice significantly reduced disease activity. HCQ treatment enhanced efferocytosis in RAW264.7 cells, while peritoneal macrophages from HCQ-treated mice showed increased efferocytotic capacity compare to PIL mice. Additionally, HCQ upregulated the expression of the TAM receptor MerTK and Gas6 on macrophages, restoring MerTK levels suppressed by pristane in the spleen of PIL mice. Inhibition of MerTK signaling by UNC2025 mitigated HCQ-mediated enhancements in efferocytosis and reversed the reduction in inflammatory mediators including IL-6 and IFN-α. HCQ-induced anti-inflammatory markers, such as PPARγ, LXR, and IL-10, were also alleviated upon MerTK blockade.ConclusionThis study provides robust in vitro and in vivo evidence that HCQ promotes macrophage efferocytosis and anti-inflammatory reprogramming via MerTK/Gas6 signaling, offering insights into potential therapeutic mechanisms in SLE management.